Pengenalan Metode Belajar Hybrid Dan Meningkatkan Motivasi Belajar Anak Panti Melalui Kegiatan Belajar Menyenangkan - Ryan Tobing (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Community service is a form of dedication by students or lecturers by pouring knowledge, experience and other things that have been obtained to go down directly to the community. The author carries out community service which is one part of the author's Field Work Practice. This community service was carried out at the Pintu Harapan Orphanage. The problem that the author helped to solve in this service began with the emergence of the Covid-19 Pandemi, this resulted in the emergence of obstacles for orphanage children such as the lack of understanding of orphanage children towards the supporting devices for the Hybrid and also restoring interest in learning for orphans during the pandemi. The implementation of the activity was carried out for approximately three months to see whether the objectives of the program were achieved and the authors were able to find answers and solutions to these obstacles. The author carried out this activity by setting the object of service, namely six 5th grade elementary school students. Implementation is used with groupwork such as Focus Group Discussion (FGD). At the end of the activity the author has found activities that can be a reference for orphanages to reduce obstacles for orphans in carrying out learning during a pandemi like this time and the author hopes that orphanage children can study diligently even during a pandemi